Interpretation and analysis of seismic and analog modeling data of triangle zone: a case study from the frontal part of western Kura foreland fold-and-thrust belt, Georgia - Alania, Victor; Enukidze, Onise; Razmadze, Alexander; Beridze, Tamar; Merkviladze, Demur; Shikhashvili, Tamar (Frontiers in Earth Science, 2023)
2D seismic reflection profiles revealed the presence of a triangle zone at the frontal part of the western Kura foreland fold-and-thrust belt of the pro-wedge of the Greater Caucasus. To understand the triangle zone geometry, seismic interpretations should be substantiated by forward kinematic modeling, supported by analog experiments. This study presents a new structural model for the region by integrating field observations, well data, and seismic reflection data. East-West directed along-strike structural variation of the frontal thrust is observed on the interpreted seismic profiles which affected the fold geometry. The Bitsmendi breakthrough fault-propagation fold gradually transits into a wedge structure in the W-E direction and is represented by the triangle zone. The seismic profiles interpretation results completely match with analog models of similar triangle zones. The analysis of the experimental results helps us to further understand the kinematic evolution of natural systems and improve seismic interpretation. The triangle zone developed in the western part of the Bitsmendi breakthrough fault-propagation fold is related to double fault-bend fold structural wedges and is characterized by the presence of passive, and active wedges, and passive-backthrust and passive-forethrust.